Предмет: Алгебра,
автор: annrur
1) Упростите выражения:
а) (х-3)(х-7)-2х(3х+5)=
б) 4а(а-2)-(а-4)=
в) 2(m+1)²-4m=
2) Разложите на множители:
а) x³-9x=
б) -5a²-10ab-5b²=
3) Упростите выражения:
(y²-2y)²-y²(y+3)(y-3)+2y(2y²+5)=
Ответы
Автор ответа:
2
а) = x^2 -7x-3x+21-6x^2-10x=-5x^2-20x+21
b)=4a^2-8a-a+4=4a^2-9a+4a
в)=2(m^2+2m+1)-4m=2m^2+2m
a)=x(x^2-9)=x(x-3)(x+3)
б)=-5(а^2+2ab+b^2)=-5(a+b)^2
3)y^4+4y^2-y^4+9y^2+10y=13y^2+10t
b)=4a^2-8a-a+4=4a^2-9a+4a
в)=2(m^2+2m+1)-4m=2m^2+2m
a)=x(x^2-9)=x(x-3)(x+3)
б)=-5(а^2+2ab+b^2)=-5(a+b)^2
3)y^4+4y^2-y^4+9y^2+10y=13y^2+10t
annrur:
А почему в а) получается -5х²-20х+21
Похожие вопросы
Предмет: Физика,
автор: sneakipigie
Предмет: Литература,
автор: Аноним
Предмет: Физика,
автор: alenalomakina2011
Предмет: Литература,
автор: LiyaKit27
Предмет: Математика,
автор: тигра14